Performance prediction of hydraulic breakers in excavation of a rock mass (Rudarsko-geološko-naftni zbornik, 2021)
The demand for the usage of hydraulic rock breakers in excavating rock masses has increased recently for environmental and economic reasons. The conventional method (i.e., drill and blasting technique) has many restrictions due to environmental aspects. In this paper, we propose a methodology for the prediction of the performance of hydraulic rock breakers in the excavation of a rock mass. The case study area is located in Northwest Egypt on the shoreline of the Mediterranean Sea. Extensive site investigation was implemented using exploration boreholes showing that the majority of the site is limestone with lenses of sands. Based on the collected rock properties, mapping of both the rock quality (RQD) and the uniaxial compressive strength (UCS) for the rock mass was conducted. Such mapping of the mechanical properties helps in the zoning of a rock mass and grouping the similar rock zones of nearly matched properties. Due to economic and machinery availability concerns, this study focuses on very small, small, and medium capacity hydraulic breakers. For each type of rock breaker, calculations of the net breaking rate (NBR) are implemented for each group of the rock with similar properties. The challenge of this methodology is that the excavation of the rock mass shall be implemented in a very limited time frame (only one year ≈ 300 workdays). Therefore, two scenarios of light-duty and medium rock breakers are applied providing the number of machines required with specifications and working days. The first scenario is assigned to medium duty machines, while the second scenario concerns very small to small rock breakers. In general, such a sequence could be adopted for other cases with different rock mass properties, hydraulic breakers specifications and any desired time frame.